Rancang Bangun Prototype Smart Campus Berbasis Automated System Untuk Meningkatkan Efisiensi Penggunaan Listrik di STMIK Antar Bangsa - Raden Ibnu Muhamad; Syarifuddin (LPPM STMIK ANTAR BANGSA, 2019)
AbstractÃ¢â‚¬â€ Microcontroller is a hardware in which there is a processor, input and output, RAM, ROM, System Bus, Contol Unit, Shift Register and Aritmatic Logic Unit. Microcontroller is able to activate some electronic devices such as led, buzzer, motor, lighting and so on. Currently, in STMIK Antar Bangsa, the activation method of lights and other electronic devices still use manual method, both in public area and classroom area so it is inefficient and causing excessive cost of electricity. For that built a system to activate every device in the classroom based automated system that will read the black and white color using the color detection sensor (IR) so that the device automatically in the classroom will be active. In addition to classrooms, in the bathroom area is also based automated system, using a distance detection sensor (HCSR) so that the light will light up when the door is closed and does not light when the door is open. With the creation of this system is expected to reduce the cost of electricity on campus STMIK Antar Bangsa and as a first step to realize the smart campus.